WORKING ON SUBORDINATE WORD RELATIONSHIPS WHEN STUDYING THE TOPIC OF "PREPOSITION" - Popova E.I (Western European Studies, 2024)
The article examines the heterogeneous nature of syntactic relations in a sentence. Their dependence on syntactic functions, on lexical and grammatical features of a word, on syntactic positions of connecting word forms is substantiated. The ways of practical mastering by students of subordinate syntactic relations, models according to which phrases are created, taking into account the choice and use of prepositions, are determined. The importance of prepositional control is proved by defining the functions of prepositions, distinguishing their syntactic meanings
Keywords: prepositions; stylistic affiliation; syntactic relations